Atypical presentation of intra-abdominal extralobar pulmonary sequestration detected in prenatal care: a case report - Costa,Márcio Rodrigues (2016)
Abstract Objective: To describe an unusual clinical presentation of intra-abdominal extralobar pulmonary sequestration in a 2-year, 9 month-old patient and assess diagnostic and treatment aspects of this pathology. Case description: An undefined intra-abdominal mass was identified in the right adrenal region in a male fetus. Postnatal evaluation with ultrasound images, computed tomography, magnetic resonance imaging and laboratory testing was insufficient to determine the nature of the lesion. After two years, laparoscopic resection of the mass and histopathological examination of the surgical specimen allowed to establish the diagnosis of intra-abdominal extralobar pulmonary sequestration. Comments: This malformation can be monitored clinically; however, surgical excision is often performed, probably due to the impossibility of attaining diagnosis with non-invasive methods, such as in the present case, in which the lesion appeared in an unusual position for intra-abdominal extralobar pulmonary sequestration. Therefore, the surgical approach seems to be the key to attain the diagnosis and establish the conduct for this type of congenital malformation.